2004
DOI: 10.1097/01.ju.0000145201.94571.67
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Reconstruction of Cloacal Malformation Can Alter Bladder Function: A Comparative Study With Anorectal Anomalies

Abstract: Patients with cloacal malformation have a high incidence of innate bladder dysfunction. However, surgical reconstruction by total urogenital mobilization can cause further deterioration of bladder function, particularly in the group with a long common channel. Urodynamic assessment is necessary to detect bladder dysfunction in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
44
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 14 publications
1
44
1
Order By: Relevance
“…The neuroanatomy of males with rectourethral fistula due to ARM has demonstrated that both pelvic splanchnic nerves come into close proximity at the level of the distal rectum and are only separated by the thin fistula itself (17). Other authors have also observed a change in urodynamics after extensive dissection needed for correction of ARM (18,19). Warne et al demonstrated 60% incidence of bladder dysfunction at presentation in 20 patients with ARM, however a change in bladder function following reconstructive surgery was noted in only one of the patients who had a recto-bladder neck fistula repaired with a combined posterior sagittal and abdominal approach (18).…”
Section: Discussionmentioning
confidence: 95%
“…The neuroanatomy of males with rectourethral fistula due to ARM has demonstrated that both pelvic splanchnic nerves come into close proximity at the level of the distal rectum and are only separated by the thin fistula itself (17). Other authors have also observed a change in urodynamics after extensive dissection needed for correction of ARM (18,19). Warne et al demonstrated 60% incidence of bladder dysfunction at presentation in 20 patients with ARM, however a change in bladder function following reconstructive surgery was noted in only one of the patients who had a recto-bladder neck fistula repaired with a combined posterior sagittal and abdominal approach (18).…”
Section: Discussionmentioning
confidence: 95%
“…The indicators of neuropathy in the context of ARA are unclear, but we consider that neuropathy affecting the bladder is one of the best indicators because of similar embryological origin of hindgut and bladder [20,21]. Morbidity related to neuropathy may be associated with the original ARA or acquired during reconstruction of anorectal and cloacal malformations [18,19,21]. Thus, urodynamic assessment may be necessary to detect bladder dysfunction in these patients.…”
Section: Introductionmentioning
confidence: 95%
“…Neuropathy and megarectum are likely to impact adversely on the functional outcome even in the presence of a good sphincter [2,[17][18][19][20]. The indicators of neuropathy in the context of ARA are unclear, but we consider that neuropathy affecting the bladder is one of the best indicators because of similar embryological origin of hindgut and bladder [20,21].…”
Section: Introductionmentioning
confidence: 97%
“…About 1:50 000 human births have a 'persistent cloaca' (2). Persistent cloaca is a potentially devastating disease, generally requiring multiple rounds of corrective surgery and, even with the best current treatments, there can be significant urological and gynaecological sequelae, including incontinence and infertility (3)(4)(5). Upper renal tract malformations are common associations.…”
Section: Introductionmentioning
confidence: 99%